Supervisi Akademik dan Profesional dalam Evaluasi Pembelajaran Pendidikan Agama Islam di Lembaga Pendidikan - Sudarmin; Zulkifli Musthan; Abd. Kadir; Muh. Shaleh (Kartika: Jurnal Studi Keislaman, 2026)
This study analyzes academic and professional supervision in the implementation of Islamic Religious Education (PAI) learning evaluation in educational institutions. The research focuses on how supervision is planned, implemented, followed up, and connected to the development of authentic and holistic assessment. This qualitative descriptive study used in-depth interviews, participatory observation, and documentation of lesson modules, supervision records, and assessment instruments involving principals, supervisors, and PAI teachers. Data were analyzed through reduction, display, and conclusion drawing. The findings show that supervision has been conducted through planning, classroom observation, feedback, and follow-up; however, its practice remains dominated by administrative control and has not consistently strengthened authentic assessment. PAI evaluation is still focused on cognitive tests, while affective and psychomotor dimensions receive limited attention. The study argues that collaborative, reflective, and value-based supervision is needed to improve teachers’ professional capacity and Islamic assessment quality. Normative foundations from the Qur’an and hadith on amanah, justice, muhasabah, ihsan, advice, and leadership responsibility strengthen the ethical basis of supervision